Si-Wu-Tang ameliorates fibrotic liver injury via modulating intestinal microbiota and bile acid homeostasis - Xiaoyong Xue (BMC, 2021)
Abstract Background Fibrotic liver injury is a progressive scarring event, which may permanently affect liver function and progress into devastating end-stage liver diseases due to the absence of effective therapies. Si-Wu-Tang (SWT), a traditional Chinese medicine formula used in clinic to treat gynecological disorders for centuries, has been investigated in recent preliminary findings for its role in alleviating chronic liver diseases. Here we aim to elucidate the therapeutic effects and possible mechanisms of SWT against fibrotic liver injury. Methods UHPLC-MS/MS was performed to investigate the chemical characterization of SWT. After intragastrically administered with carbon tetrachloride (CCl4) every 3 days for 1-week, C57BL/6 mice were orally administered with SWT (5.2, 10.4 and 20.8 g/kg) once daily for 3 weeks along with CCl4 challenge. Liver function was determined by the measurement of serum biomarkers, hematoxylin and eosin (H&E) and Masson’s trichrome staining. Intestinal inflammatory infiltration and the disruption of intestinal barrier were examined by H&E and E-cadherin immunohistochemical staining. The microbial composition of intestinal content was determined by 16S rRNA sequencing. Serum bile acids (BAs) profiling was analyzed by LC–MS/MS. Simultaneously, the expression of genes of interest was determined by qPCR and western blot. Results SWT exhibited remarkable therapeutic effects on CCl4-induced liver fibrosis, as indicated by improved collagen accumulation in livers, intestinal barrier injury and hepatic and intestinal inflammatory response. Results of 16S rRNA sequencing revealed that SWT treatment strikingly restructured intestinal microbiota in fibrotic mice by increasing the relative abundances of Bacteroides and Lachnoclostridium and decreasing the relative abundances of Alistipes and Rikenellaceae. UHPLC-MS/MS data suggested that SWT altered the composition of BAs in circulation as evidenced by increased unconjugated BAs like cholic acid and chenodeoxycholic acid but decreased conjugated BAs including taurocholic acid and taurodeoxycholic acid, compared to that in CCl4 mice. Notably, SWT efficiently improved the imbalance of BA homeostasis in livers caused by CCl4 via activating farnesoid X receptor (FXR)-fibroblast growth factor 15 enterohepatic and FXR-small heterodimer partner hepatic pathways. Conclusion SWT decreased inflammatory response, reconstructed gut microbiota-mediated BA homeostasis as well as activated FXR pathways, which eventually protected against CCl4-induced fibrotic liver injury.